2010
DOI: 10.1158/0008-5472.can-09-4104
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β1 Expression Is Regulated by miR-92 in Breast Cancer

Abstract: Estrogen receptor β1 (ERβ1) downregulation occurs in many breast cancers, but the responsible molecular mechanisms remain unclear. Here, we report that levels of ERβ1 expression are negatively regulated by the microRNA miR-92. Expression analysis in a cohort of primary breast tumors confirmed a significant negative correlation between miR-92 and both ERβ1 mRNA and protein. Inhibition of miR-92 in MCF-7 cells increased ERβ1 expression in a dose-dependent manner, whereas miR-92 overexpression led to ERβ1 downreg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 32 publications
5
67
1
Order By: Relevance
“…Moreover, in CLL B cells, miR-92a decreases pVHL expression, leading to accumulation of HIF1a and subsequently VEGF (30). Estrogen receptor ␤1 was demonstrated to be the target of miR-92a in breast cancer (31). Our current finding indicated that miR-92a represses the expression of CDH1 in ESCC.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, in CLL B cells, miR-92a decreases pVHL expression, leading to accumulation of HIF1a and subsequently VEGF (30). Estrogen receptor ␤1 was demonstrated to be the target of miR-92a in breast cancer (31). Our current finding indicated that miR-92a represses the expression of CDH1 in ESCC.…”
Section: Discussionsupporting
confidence: 52%
“…The potential role of ERb in breast cancer has been the subject of much debate and recent work in FBC by us and others shows this depends on the cell location and the type of isoforms expressed [9,44]. However, ERb is subject to complex regulation involving 3 0 UTRs [45] and microRNAs [46], and we need to further understand its biology before speculating on any role it may play in MBC.…”
Section: Discussionmentioning
confidence: 99%
“…miR-22 represses ER α expression by directly targeting its 3′ untranslated region (UTR), which induces mRNA degradation (Pandey and Picard 2009). ER β 1 is often down-regulated in breast cancers, and analysis of primary breast tumors demonstrates this may be due to a negative correlation between miR-92 and ER β 1 mRNA and protein (Al-Nakhle et al 2010). In vitro experiments confirm this finding by showing that overexpression of miR-92 decreases ER β 1 via direct targeting of the ER β 3′ UTR (Al-Nakhle et al 2010).…”
Section: Breast Cancer and Ermentioning
confidence: 99%